Metagenomic study of the microbiome and key geochemical potentials associated with architectural heritage sites: a case study of the Song Dynasty city wall in Shou County, China - Zhao, Mingyi; Li, Yanyu; Chen, Huanhuan; Chen, Yile; Zheng, Liang; Wu, Yue; Wang, Kang; Pan, Zhao; Yu, Tao; Wang, Tao (Frontiers in Microbiology, 2024)
Historical cultural heritage sites are valuable for all of mankind, as they reflect the material and spiritual wealth of by nations, countries, or specific groups during the development of human civilization. The types and functions of microorganisms that form biofilms on the surfaces of architectural heritage sites influence measures to preserve and protect these sites. These microorganisms contribute to the biocorrosion of architectural heritage structures through the cycling of chemical elements. The ancient city wall of Shou County is a famous architectural and cultural heritage site from China's Song Dynasty, and the protection and study of this site have substantial historical and cultural significance. In this study, we used metagenomics to study the microbial diversity and taxonomic composition of the Song Dynasty city wall in Shou County, a tangible example of Chinese cultural heritage. The study covered three main topics: (1) examining the distribution of bacteria in the biofilm on the surfaces of the Song Dynasty city wall in Shou County; (2) predicting the influence of bacteria involved in the C, N, and S cycles on the corrosion of the city wall via functional gene analysis; and (3) discussing cultural heritage site protection measures for biocorrosion-related bacteria to investigate the impact of biocorrosion on the Song Dynasty city wall in Shou County, a tangible example of Chinese cultural heritage. The study revealed that (1) the biofilm bacteria mainly belonged to Proteobacteria, Actinobacteria, Cyanobacteria, Bacteroidetes, and Firmicutes, which accounted for more than 70% of the total bacteria in the biofilms. The proportion of fungi in the microbial community of the well-preserved city wall was greater than that in the damaged city wall. The proportion of archaea was low—less than 1%. (2) According to the Shannon diversity index, the well-preserved portion of the ancient city wall had the highest diversity of bacteria, fungi, and archaea, and bacterial diversity on the good city wall was greater than that on the corroded city wall.